The Image of A Preacher in Efforts to Develop Islamic Propagation - Said, Nurhidayat (Jurnal Mercusuar, 2020)
The condition of the person being called to Islam (mad'u) will always change and develop in accordance with the challenges and needs it faces, in line with the rapid development of science and technology. This reality demands a change in the socio-cultural life of society, including within the da'i themselves. Every da'i is the heir of the Prophet, so their communication will be effective if they absorb the radiance of Allah's nobility and knowledge within themselves. In modern communication theory, this noble character is called 'trustworthiness' and the knowledgeable character is called 'expertness'. Several studies have shown that people tend to follow the opinion or beliefs of those they consider honest and knowledgeable.